The implementation of modern African Constitutions: Challenges and prospects - Charles Manga Fombad (Pretoria University Law Press (PULP), 2016)
In "The implementation of modern African Constitutions: challenges and prospects", the authors try to identify obstacles to constitutional implementation in Africa and, on the basis of good practice, assess how this could be overcome. A single volume like this cannot unravel the complexity of the causes and effects of, and solutions to, the problem of non-implementation of constitutions in Africa: the subject is far too intricate. Nevertheless, this study, represents a first attempt to draw attention to the issue, and hopes to open a serious debate about it and pave the way for making this issue an integral consideration in constitution-building in the future. The variety of perspectives provided in analysing the challenges to constitution-implementation in this volume should make it to appeal to academics, practitioners, policy makers and postgraduate research students interested in the intricacies of comparative African constitutional law.